Changes in the rate of nicotine metabolism across pregnancy: a longitudinal study. (3rd August 2015) - Bowker, Katharine; Lewis, Sarah; Coleman, Tim; Cooper, Sue
Abstract: Aims: Increased nicotine metabolism during pregnancy could explain why nicotine replacement therapy (NRT) appears to be less effective on smoking cessation in pregnancy than in non‐pregnant smokers, but little is known about nicotine metabolism across pregnancy. This study was conducted to determine when changes in nicotine metabolism occur during pregnancy and to describe the magnitude of these changes. Design: Longitudinal cohort study of pregnant smokers' nicotine metabolite ratio (NMR). Setting and Participants: 101 pregnant smokers recruited from hospital antenatal clinics in Nottingham, UK were asked to provide saliva samples at 8–14 weeks (n = 98), 18–22 weeks (n = 65), 32–36 weeks gestation (n = 47), 4 weeks postpartum (n = 44) and 12 weeks postpartum (n = 47). Measurements: Nicotine metabolite ratio (NMR) was measured using the ratio of cotinine to its primary metabolite trans‐3'‐hydroxycotinine. Multi‐level modelling was used to detect any overall difference in NMR between time points. The 12 week postpartum NMR was compared with the NMRs collected antenatally and 4 weeks postpartum. Findings: NMR changed over time (p = 0.0006). Compared with NMR at 12 weeks postpartum, NMR was significantly higher at 18–22 weeks (26% higher, 95% CI 12% to 38%) and 32–36 weeks (23% higher, 95% CI 9% to 35%). There was no significant difference between the 8‐14 weeks gestation or 4 weeks postpartum NMR and 12 weeks postpartum. Conclusions: Nicotine metabolism appears to be faster during pregnancy; this faster metabolism is apparent from 18 to 22 weeks of pregnancy and appears to fall by 4 weeks after childbirth.